The COVID-19 and the Assessment of the Teaching - Learning Process in Law Students - Astudillo Meza, Constanza (2023)
Introduction: The COVID-19 pandemic modified all aspects of life including the educational field, where higher education institutions implemented classes through digital platforms, in all areas of knowledge, including Law. Objective: To describe the assessment of law students regarding the virtual teaching-learning process and teaching innovation in the context of the COVID-19 pandemic in a higher education institution in northern Chile. Method: A questionnaire was applied to evaluate the participants’ evaluation of the e-learning and teaching innovation process in the context of the COVID-19 pandemic. Descriptive analyses and differences in proportions were performed. Results: The evaluation of the teaching-learning process was mostly regular. On the other hand, among the advantages, the organization of time and the possibility of visualizing the class recordings were highlighted. Conclusions: There is a need to address factors that influence the quality of learning, the causes of which are not academic.